Who is the Filipino - Velez, Jose Mari. (Quezon City GMA Radio Television News and Public Affairs)
Shows the Filipino idiosyncracies, strengths and weaknesses. Gives insights into the Filipino identity.
Host, Jose Mari Velez.
Keywords: Filipinos; Sociology